Response - Letter to the editiors - Schmidt, W.; Heinicke, K.; Wolfarth, B.; Heinicke, I. (International Journal of Sports Medicine, 2005)
Reaktion der Autoren Heinicke, K., Heinicke, I., Schmidt, W. und Wohlfarth, B.A. auf einen Kommentar von C.J. Gore und A.G. Hahn zu ihrem Artikel: Three-week traditional altitude training increases hemoglobin mass and red cell volume in elite biathlon athletes